REMOVAL OF ORGANIC MATTER IN AN UPFLOW ANAEROBIC SLUDGE BLANKET REACTOR IN THE TREATMENT OF WASTEWATERIN A SLAUGHTERHOUSE IN HUANCAVELICA - Castro Olarte, Jerson (2019)
This research evaluated a new system of primary treatment for industrial waste water, an"Anaerobic Upflow sludge blanket Reactor" (UASB) was used for the removal of organic matter. The pilot scale system was designed for the wastewater of the Municipal Slaughterhouse in Huancavelica, which was pumped after the pre-treatment (coarse screen and grit removal) to the storage tank of 350 liters for later to perform the treatment of wastewater in UASB reactor scale laboratory. The removal efficiency of organic matter in an UASB reactor was evaluated, for a hydraulic retention time (HRT) of 14 hours with a flow rate of 35mL/min, the minimum efficiency of Chemical Oxygen Demand (COD) removal was 33.66% and maximum efficiency was 76.90% in a temperature range of wastewater from 10 °C to 19 °C. Also for this HRT of 14 hours the amount of total suspended solids decreased from 524.34mg/L to 365.04mg/L, obtaining a removal efficiency of total suspended solids of 30.28%. The UASB reactor primary treatment is an alternative to remove the organic matter and total suspended solids applied for wastewater from the Municipal Slaughterhouse of Huancavelica and cities situated in places with similar climate and altitude; the design was optimized for a HRT of 14 hours for the UASB reactor, which increased the efficiency of organic matter removal.